2020
DOI: 10.1186/s10194-020-01119-0
|View full text |Cite
|
Sign up to set email alerts
|

Sensory processing patterns affect headache severity among adolescents with migraine

Abstract: Objective: To evaluate the relationship between pain catastrophizing level, sensory processing patterns, and headache severity among adolescents with episodic migraine. Background: Catastrophizing about pain is a critical variable in how we understand adjustment to pain and has a unique contribution in predicting pain intensity. Recent reports found that migraine is also related to enhanced sensory sensitivity. However, the relationship between pain severity, pain catastrophizing level and sensory sensitivity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…When the goal of alleviating or controlling pain is a requirement to achieve other vital goals, it ends up prevailing and gaining importance in the set of individual goals, promoting avoidance behaviors [ 29 ]. Furthermore, rumination constitutes the most analyzed factor within pain catastrophizing and some studies indicate that it has the greatest predictive power regarding the chronification of pain [ 42 , 43 , 56 , 57 ] and acute postsurgical pain [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the goal of alleviating or controlling pain is a requirement to achieve other vital goals, it ends up prevailing and gaining importance in the set of individual goals, promoting avoidance behaviors [ 29 ]. Furthermore, rumination constitutes the most analyzed factor within pain catastrophizing and some studies indicate that it has the greatest predictive power regarding the chronification of pain [ 42 , 43 , 56 , 57 ] and acute postsurgical pain [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also indicate a higher pain catastrophizing level in migraine patients than in healthy controls, as also seen in enhanced rumination. 25 A study examining both the independent and interactive effects of headache and self-regulatory processes on daily positive and negative affects revealed a direct link between rumination and headache. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Response to pain might be influenced by catastrophizing, and this critical variable can determine a child’s understanding and adjustment in response to pain [ 29 ]. 92 adolescents (13–18 years), including subjects with episodic migraine (n = 40) and healthy controls (n = 52), participated in a study where the Adolescent/Adult Sensory Profile (AASP), the Pain Catastrophizing Scale for children (PCS-ch), and PedMIDAS for children with migraine were determined [ 30 ]. Findings from this study [ 30 ] showed higher pain catastrophizing levels in the migraine group, where rumination and helplessness were elevated [ 30 ].…”
Section: Methods Used To Study Mood In Children With Migrainementioning
confidence: 99%
“…92 adolescents (13–18 years), including subjects with episodic migraine (n = 40) and healthy controls (n = 52), participated in a study where the Adolescent/Adult Sensory Profile (AASP), the Pain Catastrophizing Scale for children (PCS-ch), and PedMIDAS for children with migraine were determined [ 30 ]. Findings from this study [ 30 ] showed higher pain catastrophizing levels in the migraine group, where rumination and helplessness were elevated [ 30 ]. Therefore, it is valuable to investigate if children and adolescents with migraine have anxiety, depressive mood, or other forms of psychopathology [ 30 , 31 ].…”
Section: Methods Used To Study Mood In Children With Migrainementioning
confidence: 99%
See 1 more Smart Citation